The impact of extrauterine life on visual maturation in extremely preterm born infants. (September 2018) - Schwindt, Eva; Giordano, Vito; Rona, Zsofia; Czaba-Hnizdo, Christine; Olischar, Monika; Waldhoer, Thomas; Werther, Tobias; Fuiko, Renate; Berger, Angelika; Klebermass-Schrehof, Katrin
Abstract Background Extrauterine life is an important factor when considering brain maturation. Few studies have investigated the development of visual evoked potentials (VEP) in extremely preterm infants, and only a minority have taken into consideration the impact of extrauterine life. The aim of this study was to assess the normal maturation of VEP in infants born prior to 29 weeks gestational age (GA) and to explore the potential influence of extrauterine life. Methods VEP were prospectively recorded in extremely preterm infants, and principal peaks (N0, N1, P1, N2, P2, N3) were identified. The mean of peak-time and percentages of peak appearances were assessed for three GA groups (23/24, 25/26, 27/28 weeks) and four subgroups of increasing postnatal age (PNA), up to 8 weeks after birth. Results A total of 163 VEP recordings in 38 preterm infants were analyzed. With increasing GA at birth, peak-times decreased. When comparing infants with equal GA but longer extrauterine life, those with the highest PNA demonstrated the shortest VEP peak-times. However, this effect was less present in infants born prior to 25 weeks GA. Conclusion Provided that a certain maturational threshold is reached, extrauterine life appears to accelerate maturation of the visual system in preterm infants.